2017
DOI: 10.18203/2320-6012.ijrms20174602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of bupivacaine and bupivacaine plus clonidine in transversus abdominis plane (TAP) block for postoperative analgesia: a prospective, randomized, double blind, comparative study

Abstract: Background: Pain is the commonest symptom encountered postoperatively and hence multimodal analgesia is tried to overcome it. In this study, we have compared bupivacaine and bupivacaine plus clonidine in transversus abdominis plane (TAP) block for postoperative analgesia in patients undergoing lower abdominal surgeries under spinal anaesthesia. Methods: Sixty ASA I and II patients in the age range of 18-60 years undergoing various lower abdominal surgeries were randomly divided into two groups, who were operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…They found that lesser pain scores in TAP block group at 6 hour and 24 hour and suggested that TAP block was more effective than infiltration at surgical site in postoperative pain management. Another study conducted by Mir TA et al in 2016 to evaluate efficacy of bupivacaine and bupivacaine plus clonidine in TAP block for postoperative analgesia showed that addition of clonidine as adjuvant to local anaesthetic increased the duration of block and hence increased time of first rescue analgesic [12] .…”
Section: Discussionmentioning
confidence: 99%
“…They found that lesser pain scores in TAP block group at 6 hour and 24 hour and suggested that TAP block was more effective than infiltration at surgical site in postoperative pain management. Another study conducted by Mir TA et al in 2016 to evaluate efficacy of bupivacaine and bupivacaine plus clonidine in TAP block for postoperative analgesia showed that addition of clonidine as adjuvant to local anaesthetic increased the duration of block and hence increased time of first rescue analgesic [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Clonidine, alpha 2 adrenoreceptor agonist, has been very commonly used as an adjuvant with LA for epidural anesthesia,[ 8 9 ] peripheral nerve blocks,[ 6 10 ] abdominal plane block,[ 11 12 ] and local infiltration. [ 13 ] Clonidine acts by binding to presynaptic C fiber and post synaptic dorsal horn neurons and shows analgesics action by depressing the release of c-fibers, transmitter, and hyperpolarizing post synaptic dorsal horn; thus, significantly prolonging the sensory and motor block.…”
Section: Discussionmentioning
confidence: 99%